2021
DOI: 10.1515/epoly-2021-0022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of talc and diatomite on compatible, morphological, and mechanical behavior of PLA/PBAT blends

Abstract: Biodegradable nanocomposites were prepared by melt blending biodegradable poly(lactic acid) (PLA) and poly(butylene adipate-co-butylene terephthalate) (PBAT) (70/30, w/w) with diatomite or talc (1–7%). From the SEM test, the particles were transported to the interface of two phases, which acted as an interface modifier to strengthen the interfacial adhesion between PLA and PBAT. Talc and diatomite acted as nucleating agents to improve the crystallization of PBAT in the blends by DSC analysis. Moreover, adding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 41 publications
3
4
0
Order By: Relevance
“…Comparative observation of these micrographs suggests the higher agglomeration and more pronounced preferential localization of MWCNTs with higher filler content (suggested by micrographs in Figure 3c,d) in the PBAT phase. Sarul et al and Ding et al have further reported that filler particles preferentially localize in PBAT phase, however, a portion of it also moves toward the interface and PLA phase at higher filler content 44,45 . The morphology of ecovio/10 wt% MWCNT composite (see TEM micrographs in Figure 3) is consistent with earlier works.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Comparative observation of these micrographs suggests the higher agglomeration and more pronounced preferential localization of MWCNTs with higher filler content (suggested by micrographs in Figure 3c,d) in the PBAT phase. Sarul et al and Ding et al have further reported that filler particles preferentially localize in PBAT phase, however, a portion of it also moves toward the interface and PLA phase at higher filler content 44,45 . The morphology of ecovio/10 wt% MWCNT composite (see TEM micrographs in Figure 3) is consistent with earlier works.…”
Section: Resultssupporting
confidence: 87%
“…These morphologies reported in the literature are comparable to the morphology of ecovio/ 3 wt% MWCNT nanocomposites in this work. Similarly, Sarul et al and Ding et al have reported the dispersion of minority phase throughout the major phase of neat PLA/PBAT blends in the form of sea‐islands 44,45 . Based on this information and the SEM micrographs presented in Figure 2, PLA droplets as sea‐islands embedded in the PBAT component of neat ecovio used in this work can be predicted.…”
Section: Resultssupporting
confidence: 61%
“…It was further seen that the stress at yield, stress at break, and Young’s modulus of the block copolymer-based composites decreased as the CaCO 3 ratio increased beyond 5 %wt. This may be due to the agglomeration of the CaCO 3 at high ratios resulting in the reduction on the reinforcement of CaCO 3 in the composites [ 32 , 33 ]. The strain at break of the block copolymer-based composites decreased steadily as the CaCO 3 ratio increased because of the high rigidity of the CaCO 3 mineral filler.…”
Section: Resultsmentioning
confidence: 99%
“…However, the poor crystallizability of PLLA is an important limiting factor restricting its use in many applications [ 8 ]. Processed PLLAs resulted in low-crystallinity-content products that have poor heat-resistance [ 9 ]. Moreover, the biodegradability and barrier properties of PLLAs strongly depended on PLLA crystallinity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the biodegradability and barrier properties of PLLAs strongly depended on PLLA crystallinity [ 8 ]. Various methods have been investigated to enhance the crystallization ability of PLLA, such as by nucleating-agent addition [ 8 , 9 ] and plasticizer blending [ 8 ], flow-induced crystallization [ 10 ], and stereocomplexation [ 11 , 12 , 13 ]. The addition of organic and inorganic nucleating agents has been extensively and commonly used for the promotion of PLLA crystallinity by reducing the nucleating barrier and increasing nucleating sites [ 8 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%